Association Between Graphic Health Warning Labels on Cigarette Packs and Smoking Cessation Attempts in Korean Adolescent Smokers: A Cross-Sectional Study - Hye Jin Joo; Hye Jin Joo; Jae Hong Joo; Jae Hong Joo; Seung Hoon Kim; Seung Hoon Kim; Eun-Cheol Park; Eun-Cheol Park; Sung-In Jang; Sung-In Jang (Frontiers Media S.A., 2022)
Graphic health warning labels on cigarette packs inform smokers about the health risks associated with tobacco smoking. Adolescents are generally the main targets to influence by graphic health warning labels. This study investigated the association between graphic health warning labels on cigarette packs and attempts to quit smoking in South Korean adolescents. This cross-sectional study used data from the 2017 to 2019 Korea Youth Risk Behavior Web-based Survey, using multiple logistic regression for the analysis. The study population comprised 11,142 adolescents aged 12-18 years. The outcome variable was attempts to quit smoking among adolescent smokers who had seen graphic health warning labels. Attempts to quit smoking were higher among adolescent smokers who had seen graphic health warning labels compared to those who had not {boys, odds ratio (OR) = 1.72 [95% confidence interval (CI), 1.48-2.00]; girls, OR = 1.74 (95% CI, 1.33-2.28)}. The correlation was greater for adolescents who thought about the harm of smoking [boys, OR = 1.86 (95% CI, 1.60-2.16); girls, OR = 1.85 (95% CI, 1.41-2.43)] and the willingness to quit [boys, OR = 2.03 (95% CI, 1.74-2.36); girls, OR = 2.04 (95% CI, 1.55-2.68)] after seeing graphic health warning labels. Our findings indicate that graphic health warning labels on cigarette packs have the potential to lower smoking intentions of adolescents. We suggest that the use of graphic health warning labels is an effective policy-related intervention to reduce smoking in South Korean adolescents.